Reverse remodeling of the tricuspid valve complex by sinus rhythm restoration after catheter ablation - Nakatsukasa, Tomofumi; Ishizu, Tomoko; Minami, Kentaro; Kawamatsu, Naoto; Sato, Kimi; Yamamoto, Masayoshi; Machino-Ohtsuka, Tomoko; Yamasaki, Hiro; Nogami, Akihiko; Ieda, Masaki (Journal of cardiology, 2023)
Atrial fibrillation (AF) can cause right atrium enlargement and structural changes of the tricuspid valve annulus (TVA). The features of the structural changes and benefits obtained from rhythm-control therapy is unknown. We investigated how the TVA changes and whether its size decreases after rhythm-control therapy. Multi-detector row computed tomography (MDCT) was performed before and after catheter ablation for AF. TVA morphology and right atrium (RA) volume was evaluated by MDCT. The features of TVA morphology in patients with AF after rhythm-control therapy were analyzed. MDCT was performed in 89 patients with AF. The 3D perimeter was more correlated with diameter in the anteroseptal-posterolateral (AS-PL) direction than in the anterior-posterior direction. Seventy patients showed 3D perimeter reduction owing to rhythm-control therapy and the change was associated with the rate of change in the AS-PL diameter. Rate of change of the 3D perimeter was associated with that of the AS-PL diameter among TVA morphology and RA volume. We divided the subjects into three groups according to the tertiles of the TA perimeter. 3D perimeter in all groups was decreased after rhythm-control therapy. The AS-PL diameter in the 2nd and 3rd tertiles was decreased and increased TVA height in all groups. TVA in patients with AF was enlarged and flattened in the early phase, and rhythm-control therapy resulted in reverse remodeling of the TVA and in the reduction of right atrial volume. These results suggest that early AF intervention can lead to the restoration of the TVA structure. [Display omitted] •Structural changes on the tricuspid valve obtained by rhythm control therapy.•Restoring the sinus rhythm results in reverse remodeling of the tricuspid valve.•Early intervention in atrial fibrillation can restore the tricuspid valve structure.